(untitled) (Studia theodisca, 2018)
The prose of the Carinthian writer Lilian Faschinger features complex intertextual networks. By integrating as well as interweaving quotations and motives from Samuel Beckett’s Malone Dies, Thomas Bernhard’s Frost and Dante Alighieri’s Divina Commedia, her picaresque novel Magdalena Sünderin does more than merely engage in postmodern playfulness. This article investigates how Faschinger’s text makes use of its intertextual elements to ridicule the literary canon. It also poses the question whether this can be interpreted as a tongue-in-cheek feminist act against male domination in the literary scene as such.